Establishing Balance and Proprioception by Bosu Ball Training Versus Conventional Training in Soft Tissue Injuries of Knee Joint - Priya, N.Hari; P. Balaji, P. Balaji; P. Karthikeyan, P. Karthikeyan (Journal of Neonatal Surgery, 2025)
Background: To Enhance Balance And Proprioception After Lower Limb Injury In A Short Span Of Time Which Is Highly Required To Compete The Skills In The Rehabilitation Process. Objective: An Attempt Of The Study Is To Determine The Effects Of Components Like Balance And Proprioception In Individuals Sustain Soft Tissue Injuries Of Knee Joint And With The Aim To Return To Pre Injury Level Or Competitive Training To Establish The Professional Skills. The Prospective Study Has Been Aimed To Explore The Functional Outcomes Based On Unstable Platform And Conventional Training Which Have Been Challenging After Sustaining Knee Injury And Essential Movements Needed To Achieve Pre Injury Level And Performance. Eligibilty Criteria And Methodology: Depends On Selecting Individuals Who Met With Soft Tissue Injuries Grade1 And Grade 2 Of Knee Joint Will Be Identified And Confirmed By Investigation. Patients With Internal Derangement Of Knee, Fractures Of Knee, Third Degree Soft Tissue Injuries Are Excluded In The Study. The Study Based On The Effects Of Bosu Ball Training And Conventional Training In Improving The Components Of Balance And Proprioception Essential For Neuromuscular Control In Young Athletes Of Six Weeks Training. Before And After Training Have Been Recorded In Various Directions In The Concept To Record Components In Concordance With Neuromuscular Control Of An Individual. Individual Have An Exploration Of Six Weeks Training In The Division Of Rehabilitation. The Quantification Of Balance And Proprioception Relies On Star Excursion Balance Test (Sebt) In Measuring The Components Of Lower Extremity. In Sebt Neuromuscular Control Have Been Explored By Establishing Balance In One Foot And Other Foot To Propel In Multiple Directions To Record The Integrity Of Lower Extremity. Key Points Based On Intervention: Balance And Proprioception Are Motor Skills Considered As Major Components For An Athlete To Return To Sports. Rehabilitation Protocol Comprises Of Conventional Training And Training On Unstable Platform. The Components Of Motor Skills Gained Through Neuromuscular Training Has Become The Pivotal Role For Field Performance..